2017
DOI: 10.1523/jneurosci.1834-16.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Dissecting the Function of Hippocampal Oscillations in a Human Anxiety Model

Abstract: Neural oscillations in hippocampus and medial prefrontal cortex (mPFC) are a hallmark of rodent anxiety models that build on conflict between approach and avoidance. Yet, the function of these oscillations, and their expression in humans, remain elusive. Here, we used magnetoencephalography (MEG) to investigate neural oscillations in a task that simulated approach–avoidance conflict, wherein 23 male and female human participants collected monetary tokens under a threat of virtual predation. Probability of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 44 publications
8
59
0
Order By: Relevance
“…In addition, a resting state study of depression included in this review used SAM beamforming source analysis and the ICA method to describe resting state networks in individuals with MDD and found reduced correlations in networks linked to the hippocampus (Nugent, Robinson, Coppola, Furey, & Zarate, 2015). We also found one study examining the role of the hippocampus in healthy individuals performing a task designed to induce anxiety: oscillatory power, particularly in gamma band, was linked to threat probability (Khemka, Barnes, Dolan, & Bach, 2017).…”
Section: Depression and Anxietymentioning
confidence: 83%
“…In addition, a resting state study of depression included in this review used SAM beamforming source analysis and the ICA method to describe resting state networks in individuals with MDD and found reduced correlations in networks linked to the hippocampus (Nugent, Robinson, Coppola, Furey, & Zarate, 2015). We also found one study examining the role of the hippocampus in healthy individuals performing a task designed to induce anxiety: oscillatory power, particularly in gamma band, was linked to threat probability (Khemka, Barnes, Dolan, & Bach, 2017).…”
Section: Depression and Anxietymentioning
confidence: 83%
“…As such, defining spatial discrimination is arguably a statistical problem. The proposed framework has also been used extensively to model laminar sources (Bonaiuto et al, 2017(Bonaiuto et al, , 2018Troebinger et al, 2014) in MEG as well as make probabilistic statements about deep structure activity (Khemka, Barnes, Dolan, & Bach, 2017;Meyer et al, 2017b) where spatial precision is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…In later fMRI and magnetoencephalographic studies, the hippocampal role in approach‐avoidance conflicts was confirmed and elucidated in more detail (Khemka, Barnes, Dolan, & Bach, ; Loh et al , ; O'Neil et al , ).…”
Section: Introductionmentioning
confidence: 89%